2010
DOI: 10.1109/tsc.2010.10
|View full text |Cite
|
Sign up to set email alerts
|

An Autonomic Service Delivery Platform for Service-Oriented Network Environments

Abstract: I would like to thank my brother, Tom, for always being there for his little brother.Your courage is an inspiration to me, and I certainly owe you at least partially for my interest in technology. I am proud to have you as a brother and grateful for your presence in my life.Last, but surely not least, I am forever indebted to my parents for everything they have given me. Mom, thank you for all that you have done in every part of my life. Dad, I owe so much to you and I strive every day to make you proud of me.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In this instance, whereas the baseline runs took approximately two minutes to complete 1000 requests, when we introduced the Interface Faults, we found that each test run took approximately 69 minutes to complete. (ii) Average number of POI per test (Test [1][2][3][4][5][6] The output from the NSD showed that in the presence of Interface Faults, the NSD still returned a MonitorLocationInformation2 object, but each object contained zero POI. This output from our experiments demonstrates that our DBS-EF triggered successfully the abnormal behavior of the NSD as expected such that we are able to observe how severely the system was affected, e.g.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In this instance, whereas the baseline runs took approximately two minutes to complete 1000 requests, when we introduced the Interface Faults, we found that each test run took approximately 69 minutes to complete. (ii) Average number of POI per test (Test [1][2][3][4][5][6] The output from the NSD showed that in the presence of Interface Faults, the NSD still returned a MonitorLocationInformation2 object, but each object contained zero POI. This output from our experiments demonstrates that our DBS-EF triggered successfully the abnormal behavior of the NSD as expected such that we are able to observe how severely the system was affected, e.g.…”
Section: Results and Analysismentioning
confidence: 99%
“…Service-Oriented Architectures (SOA) provides a logical architecture for constructing these service-based applications [2]. Furthermore, SOC and SOA facilitate the agile choice of services according to the needs of the service consumer, such that services can be swapped out for those that are functionally equivalent [3].…”
Section: Introductionmentioning
confidence: 99%
“…[26] propose mechanisms that are able to adaptively adjust their parameters based on the past behaviour of participants. An example of economically-inspired market infrastructures is provided by [14] who present a self-optimising infrastructure platform for service delivery using economic (congestionbased) pricing, but only consider the infrastructure level, and not the market level of the platform. [6] study the mapping of high-level business objectives to lower level objectives in order to enable autonomic optimisation.…”
Section: Related Workmentioning
confidence: 99%
“…An autonomic Service Delivery Platform (SDP) is proposed in [62] that host cloud services. We see an opportunity in applying the feedback control theory in building adaptive SDPs.…”
Section: Ref and V K Are Target And Current Sensor Measurements Resmentioning
confidence: 99%